2002
DOI: 10.1577/1548-8659(2002)131<0271:ssmahu>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Survival, Movement, and Habitat Use of Age-0 Rainbow Trout in the Henrys Fork of the Snake River, Idaho

Abstract: We quantified seasonal abundances, apparent survival rates, movements, and habitat use of age‐0 rainbow trout Oncorhynchus mykiss in a 25‐km reach of the Henrys Fork of the Snake River, Idaho, to determine what factors limit recruitment to the population. Natural production of rainbow trout occurred in each year of the study (1995‐1997) and ranged from 158,000 to 306,000 age‐0 fish each summer. No significant loss of age‐0 rainbow trout occurred between summer and autumn; suitable habitat was present throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…Evidence also exists that suggests that the availability of winter habitat limits RBT recruitment in the Snake River. A recent study in the Henry's Fork of the Snake River showed that age-0 RBT survived only where complex bank habitat was present, limiting RBT to lower elevation locations (Mitro and Zale 2002).…”
Section: Spatial Patterns Of Hybridizationmentioning
confidence: 99%
“…Evidence also exists that suggests that the availability of winter habitat limits RBT recruitment in the Snake River. A recent study in the Henry's Fork of the Snake River showed that age-0 RBT survived only where complex bank habitat was present, limiting RBT to lower elevation locations (Mitro and Zale 2002).…”
Section: Spatial Patterns Of Hybridizationmentioning
confidence: 99%
“…Recently, flow regime was identified as a factor influencing the invasion success of RBT; in particular, a match between timing of fry emergence and months of low flow appears to be associated with successful invasion (Fausch et al 2001). Evidence also exists that suggests that the availability of winter habitat limits RBT recruitment in the Snake River (Idaho), and that age)0 trout survived only where complex bank habitat was present (Mitro and Zale 2002). Consequently, an analysis of flow regimes and habitat types within the upper Kootenay River drainage may aid in predicting which tributaries are at greatest risk of RBT invasion, a pre-requisite to hybridization with native WCT.…”
Section: Environmental Correlates Of Hybridizationmentioning
confidence: 99%
“…They found evidence that availability of winter habitat limited rainbow trout recruitment in the Henrys Fork. Most river sections in the Henrys Fork had only simple bank habitat and did not support age-0 rainbow trout throughout winter (Mitro and Zale 2002a). The winter habitat that supported age-0 trout was complex bank habitat, and age-0 trout survived throughout winter only where such habitat was present, primarily in the Box Canyon river section.…”
Section: Introductionmentioning
confidence: 98%
“…In a study of rainbow trout (Oncorhynchus mykiss) recruitment in the Henrys Fork of the Snake River, Idaho, Mitro and Zale (2002a) investigated when apparent mortality of age-0 trout occurred seasonally and where recruitment occurred in a 25-km reach of the river system. They found evidence that availability of winter habitat limited rainbow trout recruitment in the Henrys Fork.…”
Section: Introductionmentioning
confidence: 99%